PELAKSANAAN GENERAL SERVICE RULES OLEH PRAMUSAJI DI FOX HOTEL PEKANBARU - Arbi Sagita; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Hotels include business ventures that emphasize the sale of services. One of the activities carried out by the company to achieve sales targets is to implement good and efficient service to consumers. The stages of implementing this kind of service are efforts to increase service sales due to the intense competition that is happening at this time. This study aims to find out how the General Service Rules are implemented by waiters at Fox Hotel Pekanbaru. This study uses a qualitative method with a descriptive approach in which researchers will collect data from informants to find out the issues raised regarding the implementation of General Service Rules by waiters at Fox Hotel Pekanbaru. While collecting data in this study using observation, interviews, and documentation. From the research results, the indicators are handling the reservation, greeting the guest, seating the guest, beverage suggestion, presenting menu, serving beverage and iced water, taking orders, writing order slips, serving the food, clearing up, crumbing down, payment bills, and greetings. The results of the study show that the implementation of general service rules by the waiters at Fox Hotel Pekanbaru is in accordance with service delivery in general. In the implementation of general service rules there are several obstacles, namely miss communication between employees, and a lack of employees in the F&B Service section. Keywords: implementation, general service rules, waiters